Photoluminescent films of nanocrystalline silicon doped with metals - Kaganovich, E.B.; Kirillova, S.I.; Manoilov, E.G.; Primachenko, V.E.; Svechnikov, S.V.; Venger, E.F.; Bazylyuk, I.R. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
Effects of electropositive (Au, Ag, Cu) and electronegative (Al, In) metal impurities are investigated from the viewpoint of photoluminescent and electronic properties of nanocrystalline silicon films prepared by laser ablation when depositing them onto a silicon substrate. Measured are time-resolved photoluminescence e. It was ascertained that only Au could essentially increase intensity and stability of photoluminescence, increase its relaxation time by three orders of magnitude as well as decrease the density of states near the film-substrate boundary. It has been shown that the metal impurities provide an essential effect on photovoltage arising in films of nanocrystalline Si as well as the capture of non-equilibrium electrons by traps both in films themselves and at the substrate boundary.